2012
DOI: 10.1111/j.1365-2702.2012.04068.x
|View full text |Cite
|
Sign up to set email alerts
|

Mokken scaling of the Caring Dimensions Inventory (CDI‐25)

Abstract: The results using the Caring Dimensions Inventory will help to identify how caring in nursing is perceived by nursing students in Turkey. Repeating this study in different groups such as working nurses will help to determine nurses who work in clinical settings perceive caring in nursing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…Studies that focus on perceptions of nurses about car- as their competency (Geçkil et al, 2008;Wysong & Driver, 2009), since they believe good technical skills reduce their discomfort and lead to less pain (Ayyub et al, 2015). In this study, aspects of care such as observing the effects of being technically competent with a clinical procedure, consulting with the doctor, instructing a patient about aspects of care, listening to a patient, explaining the clinical procedure to a patient and being with a patient during the clinical procedure were among the endorsed items which are congruent with two previous studies (Akansel et al, 2012;Watson et al, 2003) TA B L E 3 Mokken scale of CDI-25 items (N = 260) although the order of the items is different. Items referring to technical aspects of nursing were found to be among the highly endorsed items.…”
Section: Perceptions Of Caring Among Nursessupporting
confidence: 87%
See 2 more Smart Citations
“…Studies that focus on perceptions of nurses about car- as their competency (Geçkil et al, 2008;Wysong & Driver, 2009), since they believe good technical skills reduce their discomfort and lead to less pain (Ayyub et al, 2015). In this study, aspects of care such as observing the effects of being technically competent with a clinical procedure, consulting with the doctor, instructing a patient about aspects of care, listening to a patient, explaining the clinical procedure to a patient and being with a patient during the clinical procedure were among the endorsed items which are congruent with two previous studies (Akansel et al, 2012;Watson et al, 2003) TA B L E 3 Mokken scale of CDI-25 items (N = 260) although the order of the items is different. Items referring to technical aspects of nursing were found to be among the highly endorsed items.…”
Section: Perceptions Of Caring Among Nursessupporting
confidence: 87%
“…Geçkil et al (2008) emphasized that the protection of privacy by nurses afforded the most satisfaction to patients from the nursing care they receive. In this study "providing privacy for a patient" was the most endorsed item which is the same as a previous study with Turkish nursing students (Akansel et al, 2012).…”
Section: Perceptions Of Caring Among Nursesmentioning
confidence: 52%
See 1 more Smart Citation
“…Previous research using this instrument showed differences in the perception of caring regarding nurses' age and sex (R. and also differences regarding the clinical work area, between medical and surgical wards (Lea & Watson, 1999). The CDI-25 has been used to study the perceptions of caring in nursing among United Kingdom and Spanish nurses (Akansel et al, 2013;R. Watson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Caring and nursing have always been thought of synonymously ( Vance, 2009 ). There are many definitions of nursing, such as holism, caring, teaching, advocacy, supporting, promoting, maintaining and restoring health are all components of nursing practice ( Akansel, Watson, Aydin, & Ozdemir, 2011 ).…”
Section: Introductionmentioning
confidence: 99%